2022
DOI: 10.35942/ijcfa.v4i1.229
|View full text |Cite
|
Sign up to set email alerts
|

Working Capital Management and Financial Performance of Small and Medium Enterprises in Garissa County, Kenya

Abstract: Small and medium-sized enterprises (SMEs) in the County of Garissa have had a dwindling net profit between 2007 until 2013. Success has been marked by several hurdles that include improper business records, substandard technical competence, illiteracy in matters of finance, and mismanagement of working capital. As a result, the overarching purpose of the study was to investigate the influence of working capital management on the financial performance of SMEs in the Kenyan county of Garissa. The study was motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…This shows that inventory turnover period had a negative relationship with financial performance of the sampled firms. The findings concur with those of Ahmed and Mwangi (2022) who found that inventory management3had a negative relationship with financial performance. However, they are different from those of Park and Kim (2020) who found that inventory turnover positively related with business financial performance.…”
Section: Correlation Analysissupporting
confidence: 90%
“…This shows that inventory turnover period had a negative relationship with financial performance of the sampled firms. The findings concur with those of Ahmed and Mwangi (2022) who found that inventory management3had a negative relationship with financial performance. However, they are different from those of Park and Kim (2020) who found that inventory turnover positively related with business financial performance.…”
Section: Correlation Analysissupporting
confidence: 90%
“…A lower APP may indicate that it is not fully utilizing possibilities to delay supplier payments (Kumaraswamy, 2016). The transactional cost theory was founded by Ferris in 1981, and is a notable theory used to explain the relationship between the accounts payable period and firm performance (Ahmed and Mwangi, 2021). The theory contends that firms can operate efficiently by reducing the transaction costs associated with the delay in the accounts payable (Ferris, 1981).…”
Section: Literature Review and Hypotheses Development 21 A Brief Over...mentioning
confidence: 99%
“…Providing credit to customers may also positively affect firm sales as it allows price differentiation, serves as a warranty for product quality, and cultivates long-term relationships with customers (Wilson and Summers, 2002;Long et al, 1993). In contrast, overinvestment in working capital can have a negative impact on financial performance as well as shareholders' value (Ahmed and Mwangi, 2022). Furthermore, having too much working capital may prevent enterprises from undertaking value-adding investment projects in the short term (Ek and Guerin, 2011).…”
Section: Ijppm 734mentioning
confidence: 99%
“…If the working capital is positive, the company has sufficient current assets to conduct its operations and repay its debt. It provides investors and shareholders with confidence in the company's financial stability (Ahmed and Mwangi, 2022). However, if working capital is negative, the company lacks sufficient current assets and is likely to experience operational disruptions in the future, leading to a decline in financial performance (Haralayya, 2022; Abdulnafea et al ., 2022).…”
Section: Related Literature and Hypotheses Developmentmentioning
confidence: 99%